PRO-FIT-CARE study: the feasibility assessment of a pilot online exercise intervention for persons living with obesity and female infertility - K. P. Wadden; N. Hollohan; T. Furneaux; R. Maher; C. M. Barrett; D. Fuller; F. Basset; D. Murphy; D. Murphy; S. Murphy; S. Murphy; S. Healey; et al. (Frontiers Media S.A., 2024)
IntroductionModerate-to-high physical activity participation is associated with a reduced risk of infertility. Yet, exercise interventions that target cardiorespiratory fitness, independent of weight loss, are lacking in obesity and female fertility research.PurposeThe primary objective of the PRO-FIT-CARE (PROmoting FITness for CArdiometabolic & REproductive Health) study was to assess the feasibility of a moderate-to-high-intensity online exercise program for persons with obesity and female infertility.MethodsFeasibility, safety, acceptability, and efficacy were assessed by examining: (1) recruitment and consent rate, (2) study retention, (3) adverse events, (4) participant satisfaction, (5) adherence, and (6) cardiorespiratory fitness.ResultsEleven of thirty-two women contacted agreed to participate in the program (34.4% consent rate). Eight participants (72.7%) completed the study. One musculoskeletal injury was reported. There was a 30% adherence rate based on prescribed exercise intensity (60%-80% of heart rate maximum). One of eleven participants attended 80% of the exercise intervention. Based on a weekly satisfaction survey, the program had an overall high level of satisfaction. Compared to sex and age normative data, post-intervention, two of eight participants improved their cardiorespiratory fitness percentile rank.ConclusionThe study highlights challenges with adherence to an online exercise program. While the program was safe and participants reported high levels of program satisfaction, approaches to improve adherence must be incorporated.